2020
DOI: 10.1016/j.pec.2020.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Concerns of women regarding pregnancy and childbirth during the COVID-19 pandemic

Abstract: Highlights Pregnant and recently delivered women reported behavior changes due to COVID-19. Preventive measures (e.g. social distancing) were used by respondents. Negative changes in mental health, such as increased stress, were also reported. Employment and fiscal security decreased; postpartum alcohol consumption increased. Healthcare access remained stable for most.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 23 publications
7
85
1
6
Order By: Relevance
“…In our cohort of pregnant Black women from the Midwest, a high proportion reported being very much worried about their child, family members, friends, and themselves getting infected. This mirrors results found in another study conducted in the Midwest among a diverse group of pregnant and postpartum women where a high proportion of women similarly reported being very concerned about COVID‐19 (Ahlers‐Schmidt et al., 2020).…”
Section: Discussionsupporting
confidence: 80%
“…In our cohort of pregnant Black women from the Midwest, a high proportion reported being very much worried about their child, family members, friends, and themselves getting infected. This mirrors results found in another study conducted in the Midwest among a diverse group of pregnant and postpartum women where a high proportion of women similarly reported being very concerned about COVID‐19 (Ahlers‐Schmidt et al., 2020).…”
Section: Discussionsupporting
confidence: 80%
“…In Italy, Ravaldi et al [ 28 ] reported birth expectations completely changed after the onset of COVID-19 to include fear, sadness and uncertainty. Ahlers–Schmidt et al [ 29 ] carried out an electronic survey with a 51% response rate of pregnant women or mothers of infants less than 12 months, 82.5% of whom reported changes in mental status, including an increase of anxious thoughts related to the COVID-19 pandemic of 50%. In Italy, almost half of the women (46%) in an interview reported high anxiety regarding risks of vertical transmission of the disease [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many people have lost their jobs and income, including people in households with pregnant women. This further increases the mental health burden of pregnant women [27][28][29]. In addition, pregnant women who work also face severe psychological stress [30].…”
Section: (Covid-19) Pandemicmentioning
confidence: 99%